2020
DOI: 10.1016/j.anl.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Management of extracranial arteriovenous malformations of the head and neck

Abstract: The purpose of this study was to review the outcomes of the different therapies for extracranial head and neck arteriovenous malformations (AVMs).AVMs are high-flow congenital vascular anomalies. They are composed of a complex system of vessels directly connecting feeding arteries to draining veins forming a nidus.They may be potentially life-threatening due to progressive symptoms and infiltrative disease. Extracranial AVMs most commonly affect the head and neck area (47.4%) followed by the extremities (28.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 46 publications
(53 reference statements)
0
44
0
Order By: Relevance
“…The most common complications reported skin necrosis owing to over injection and re ux of ethanol 4,9 , especially in the periorbital skin. Park et al reported that intra-arterial ethanol injection causes skin necrosis because tiny, angiographically invisible normal arteries become exposed to ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications reported skin necrosis owing to over injection and re ux of ethanol 4,9 , especially in the periorbital skin. Park et al reported that intra-arterial ethanol injection causes skin necrosis because tiny, angiographically invisible normal arteries become exposed to ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of embolization and surgical resection has become recently the treatment of choice. The main goal of both is the complete devascularization of the vascular lesion [6].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used endovascular procedure is super-selective embolization, a technique in which an embolic agent is delivered via a catheter to obstruct blood flow within a target vessel [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vessels walls are thick and muscular, with no clear elastic laminae (black arrows). Some venules and thin-walled dilated capillaries are also visible in the upper dermis (white arrows)(and is thus appropriate for superficial lesions), enables longer injection time and reduces imaging artifacts 2.…”
mentioning
confidence: 99%